NIKAH MUT'AH RIWAYATMU KINI (Tela’ah Tentang Pelaksanaan Sunnah Nikah Mut’ah Melalui Pendekatan Hadits Dan Sirah Nabawiyah) - Uswatun Hasanah (AL-FIKRA, 2017)
This paper concludes that when looking at the history of hadith and sirah nabawiyyah around the legitimacy and the prohibition of marriage mut'ah understood that mut'ah marriage is not a good sunnah to do. This conclusion denied the opinion of al-Thabathabai in particular and the Shi'ite group in general who stated that the Shia still allow and allow the implementation of the Mut'ah marriage in the present. This research supports the opinion of al-Nawawi as an ambassador of the Sunni group who said about the salting of mut'ah marriage